Curcumin nanospheres and nanorods: Synthesis, characterization and anticancer activity. (January 2022) - Rajasekar, Abbu; Devasena, Thiyagarajan; Suresh, Subramaniyam; Senthil, Bakthavachalam; Sivaramakrishnan, Ramachandran; Pugazhendhi, Arivalagan
Graphical abstract: Highlights: Curcumin nanospheres and nanorods were synthesized by antisolvent precipitation. Characterization studies confirms the nano size of nanospheres and nanorods. Both nanoparticles exhibited excellent in vitro cytotoxicity against HepG2 cells. Morphological variation of nano materials influences the apoptotic cell death. Abstract: Development in nanotechnology and its biological application have progressively contributes to the interaction of nanoparticles with cells which helps in treating/diagnosing cancer like diseases. In order to understand the morphological transformation of drug nanoparticles interaction on cancerous cells, we prepared curcumin nanorods (CNRs) and curcumin nanospheres (CNSs) by antisolvent precipitation process. The size, surface charge and morphology were analyzed by Dynamic Light Scattering (DLS) and High Resolution Transmission Microscope (HRTEM). The size of both the nanoparticles ranges below 50 nm and the zeta potential showed the negative surface charge. Powder X-ray Diffraction (PXRD) and Fourier Transformer Infra-Red spectroscopy (FTIR) studies revealed the crystal systems (monoclinic and orthorhombic forms) of curcumin nanoparticles. The cytotoxicity of these drugs was tested using MTT assay, where CNRs exhibited a little more anticancer activity and apoptosis than CNSs in HepG2 cells. Hence, we suggest that the morphological variation may act as another factor, which influences apoptotic cell death in spite of the surface charge.